RETRACTED : The Influence of Brand Image, Brand Trust, and Advertising on the Purchase Decision of Wardah Cosmetic Products in Lima Plaza in South Jakarta - Mutia Wanda Putry; Resti Hardini; Kumba Digdowiseiso (Journal of Social Science)
This research aims to analyze the effect of brand image, brand trust and the advertising of product purchase cosmetics Products in lima plaza area of South Jakarta. This research data using primary data in the form of a questionnaire to 100 respondents who decide to purchase cosmetic products by the method of linear regression Wardah double processed using the software SPSS 17.0. From data that have met the test of validity, reliability test, and a test of regression equation obtained classical assumptions as follows: Y= 0,365X1 + 0,219X2 + 0,302X3. Where to purchase decision variable (Y), brand image (X1), brand trust (X2) and advertising (X3). Feasibility test of the model shows that a third of the free variables examined proven positive effect simultaneously and significantly to variables bound. Through partial hypothesis testing can be known that brand image, brand trust and ads proved positive effect respectively against the decision of purchase i.e. amounting to 53.50% meaning 53.50% variable of the buying decision can be explained by the variables are free i.e. brand image, brand trust and ads while the rest 46% is explained by other variables that do not enter into this research.